South African physician emigration and return migration, 1991–2017: a trend analysis. Issue 5 (29th March 2021) - Nwadiuko, Joseph; Switzer, Galen E; Stern, Jaime; Day, Candy; Paina, Ligia
Abstract: Although critical for understanding health labour market trends in low- and middle-income countries (LMICs), longitudinal LMIC health worker emigration and return migration trends are not routinely documented. This article seeks to better understand SA's trends in physician emigration and return migration and whether economic growth and related policies affect migration patterns. This study used physician registry data to analyse patterns of emigration and return migration only among SA-trained physicians registered to practice in top destination countries such as Australia, Canada, New Zealand, the USA or the UK between 1991 and 2017, which represent the top five emigration destinations for this group. A linear regression model analysed the relationship between migration trends (as dependent variables) and SA's economic growth, health financing and HIV prevalence (as independent variables). There has been a 6-fold decline in emigration rates from SA between 1991 and 2017 (from 1.8% to 0.3%/year), with declines in emigration to all five destination countries. About one in three (31.8% or 5095) SA physicians returned from destination countries as of 2017. Annual physician emigration fell by 0.16% for every 100 rise in SA GDP per capita (2011 international dollars) (95% confidence interval −0.60% to −0.086%). As of 2017, 21.6% (11 224) of all SA physicians had active registration in destination nations, down from a peak of 33.5% (16 366) in 2005, a decline largely due to return migration. Changes to the UK's licensing regulations likely affected migration patterns while the Global Code of Practice on International Recruitment contributed little to changes. A country's economic growth might influence physician emigration, with significant contribution from health workforce policy interventions. Return migration monitoring should be incorporated into health workforce planning.